2017
DOI: 10.1111/bpa.12454
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis animal models: a clinical and histopathological perspective

Abstract: There is a broad consensus that multiple sclerosis (MS) represents more than an inflammatory disease: it harbors several characteristic aspects of a classical neurodegenerative disorder, that is, damage to axons, synapses and nerve cell bodies. While we are equipped with appropriate therapeutic options to prevent immune-cell driven relapses, effective therapeutic options to prevent the progressing neurodegeneration are still missing. In this review article, we will discuss to what extent pathology of the progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
155
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 188 publications
(160 citation statements)
references
References 143 publications
3
155
0
2
Order By: Relevance
“…It is well documented that ER stress plays a critical role in various myelin disorders by regulating oligodendrocyte viability (Lin & Popko, ; Clayton & Popko, ; Volpi et al, ). MS and EAE are believed to be initiated by an autoimmune reaction against oligodendrocytes and myelin (Frohman et al, ; Bradl & Lassmann, ; Kipp et al, ). Recent studies show that ER stress modulates oligodendrocyte viability during EAE, and subsequently influences the disease development (Lin et al, ; Hussien et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well documented that ER stress plays a critical role in various myelin disorders by regulating oligodendrocyte viability (Lin & Popko, ; Clayton & Popko, ; Volpi et al, ). MS and EAE are believed to be initiated by an autoimmune reaction against oligodendrocytes and myelin (Frohman et al, ; Bradl & Lassmann, ; Kipp et al, ). Recent studies show that ER stress modulates oligodendrocyte viability during EAE, and subsequently influences the disease development (Lin et al, ; Hussien et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…During EAE pathogenesis, inflammation causes oligodendrocyte death and demyelination, and then oligodendrocyte death and demyelination promote inflammation, forming a vicious circle (Frohman et al, ; Bradl & Lassmann, ; Kipp et al, ). While we showed that there was no significant difference in inflammatory cell infiltration in the CNS of ATF6α K O mice and ATF6α WT mice, flow cytometry analysis showed a trend of decreased inflammatory cell infiltration in the whole spinal cord of ATF6α KO mice with EAE.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, the apoptosis of oligodendrocytes appears after 2 days, as a consequence of cuprizone intoxication, before demyelination is obvious (Buschmann et al, ). The demyelination is usually evident 3 weeks after the start of cuprizone administration and correlates with immense microgliosis, astrogliosis, and axon damage (Doan et al, ; Kipp et al, ). Six weeks after cuprizone ingestion, demyelination occurs globally, but it is most prominent in the corpus callosum and posterior cerebellar peduncles and is referred to as “acute demyelination.” Acute demyelination is followed by spontaneous remyelination, when a cuprizone diet is replaced by normal chow.…”
Section: Toxin‐induced Demyelination Modelsmentioning
confidence: 99%
“…Biozzi ABH mice display the pathological hallmarks of MS, such as inflammatory‐mediated demyelination, together with neurodegeneration (Hampton et al, ; Jackson, Lee, Nikodemova, Fabry, & Duncan, ; Peferoen et al, ). During relapses, these mice undergo excessive demyelination, where demyelination areas are filled with T cells, macrophages, and immunoglobulin depositions (Amor et al, ; Baker et al, ; Kipp et al, ). It is interesting that autoimmune tolerance can eliminate relapses, but permanent neurological deficits are accumulated slowly (Pryce et al, ).…”
Section: Selection Of Animals In Eaementioning
confidence: 99%
“…Disturbance of oligodendrocyte development and maintenance is associated with major diseases of the CNS including multiple sclerosis (MS) (Barnett and Prineas ; Prineas and Parratt ; Kipp et al . ), stroke (Pantoni et al . ; Fern et al .…”
mentioning
confidence: 99%